Factors Affecting Teachers' Performance in Public Elementary Schools in Schools Division of City of Meycauayan, Bulacan - Paz, Rosalia M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The major concern of this study was to determine the impact of factors affecting teachers' performance of public elementary teachers. The study used the descriptive- correlational method of research in which standardized instruments were the primary data gathering tool. The study respondents were 166 or 55.41 percent of public elementary teachers in cluster A of the Division of Meycauayan City. The results of the study revealed that for the level of contributing factors in teaching performance, much contribution overall rating was obtained in the following factors: (1) Person-related factor, (2) School-related factor, (3) Learner-related Factor and (4) Community-related factor. Meanwhile, on the level of teaching performance, it was revealed based on the result of the study that the following factors were accomplished in terms of (1) Content, Knowledge, and Pedagogy, (2) Learning Environment and Diversity of Learners, (3) Curriculum and Planning, (4) Assessment and Reporting and (5) Plus Factors. The study's findings indicated that the contributing factors in teaching performance such as person-related Factor, school-related Factor, learner-related Factor, and community-related factor correlated to the level of teachers' performance in terms of the five key result areas. The findings of the analysis revealed that the null hypothesis is rejected; hence, the contributing factors significantly impacted teachers' teaching performance.